A Rare Case of Fahr's Disease with Epileptic Seizures with Severe Hypocalcemia and Calcifications - D, Karthik; Jadhav, Renuka; Mane, Shailaja; Mitra, Priyanka; Raval, Nidhish (Journal of Neonatal Surgery, 2025)
Fahr’s syndrome is a condition defined as bilateral striato-pallido-dentate calcinosis, a neurodegenerative disease with radiological findings of symmetrical and bilateral idiopathic calcifications of the cerebellum, periventricular white matter, and basal ganglia. Clinical correlation with radiological and a calcium metabolism panel is crucial in differentiating between Fahr’s disease and Fahr’s syndrome. In this case, the patient presented with clinical features of hypocalcemic tetany with global developmental delay and had an incidental radiological finding of Fahr syndrome.